Challenges Facing Smallholder Indigenous Chicken Farmers in Accessing Market Information: A Case Study of Misungwi District, Mwanza, Tanzania - Kikoti, William Valentino; Rwiza, Kamgisha (New Advances in Business, Management and Economics Vol. 7, 2025)
Indigenous chicken farming in Tanzania is an important economic activity that has the potential to improve the livelihoods of smallholder farmers, yet their profitability remains low due to a lack of information required at the markets. This study is to review the challenges Tanzanian smallholder chicken farmers face while trying to obtain market information in the Misungwi district. This study was carried out in four purposefully selected villages in the Misungwi district. This study used a sample size of forty respondents. The study employed a survey, interview and desk study research design and both qualitative and quantitative research approaches were used. Stakeholders were interviewed, including four traders, four middlemen, and two extension officers. Quantitative data were analysed by using analytical models and Microsoft Excel spreadsheets, while qualitative data were analysed using a content analysis procedure. The result of the study revealed that the price information has an impact on improving the bargaining ability of smallholder chicken farmers in the marketing system. The constraints to accessing market information in the study area are associated with the lack of information services, an inadequate number of extension officers, high illiteracy, a lack of awareness of the market information services, and a lack of means and facilities by which information can be easily accessible. It is therefore suggested that there is a need for the Misungwi district council to place more weight on better practices on access to relevant, current, and appropriate market information for smallholder chicken farmers on prices based on the information provided, which will increase their bargaining power for their chicken.